2013
DOI: 10.1017/s0033291713002468
|View full text |Cite
|
Sign up to set email alerts
|

Childhood stressors in the development of fatigue syndromes: a review of the past 20 years of research

Abstract: Our review confirms that exposure to childhood stressors is associated with the subsequent development of fatigue syndromes such as CFS and FM, and related symptoms. Further studies are needed to identify the mechanisms underlying these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 101 publications
(172 reference statements)
2
22
0
1
Order By: Relevance
“…Reduced efficacy was weakly related to life stress only in the sample of depressed patients. An association between life stress operationalized as childhood trauma and fatigue, which is quite similar to the emotional exhaustion component of burnout, has recently been found by Borsini, Hepgul, Mondelli, Chalder, and Pariante (2013). Similarly, Carlier, Lamberts, and Gersons (1997) found a significantly increased level of emotional exhaustion in policemen that had experienced traumatic events and suffered from PTSD.…”
Section: Discussionmentioning
confidence: 75%
“…Reduced efficacy was weakly related to life stress only in the sample of depressed patients. An association between life stress operationalized as childhood trauma and fatigue, which is quite similar to the emotional exhaustion component of burnout, has recently been found by Borsini, Hepgul, Mondelli, Chalder, and Pariante (2013). Similarly, Carlier, Lamberts, and Gersons (1997) found a significantly increased level of emotional exhaustion in policemen that had experienced traumatic events and suffered from PTSD.…”
Section: Discussionmentioning
confidence: 75%
“…Previous work has also suggested an increased prevalence of childhood physical, emotional and sexual abuse in those with idiopathic chronic fatigue and chronic fatigue associated with medical and psychiatric illness [ 50 ]. Borsnini et al [ 51 ] have also confirmed childhood stressors to increase the possibility of subsequent CFS/ME. We do not routinely explore this area in detail as it seldom helps to reduce the symptoms of CFS/ME but does have the possibility of aggravating matters by raising stress and anxiety levels.…”
Section: Introductionmentioning
confidence: 96%
“…However, a consistent pattern of circulating cytokine or chemokine levels has not been reported (Menzies, Lyon, Elswick, Montpetit, & McCain, ; Rodriguez‐Pintó et al, ). Thus, symptoms of FM are unlikely to follow from elevations of circulating cytokines per se but might be associated with individual differences in the inflammatory response to ongoing stressful experiences (Borsini, Hepgul, Mondelli, Chalder, & Pariante, ; Feng et al, ).…”
mentioning
confidence: 99%